2018
DOI: 10.1002/mbo3.615
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity of thermophiles with biomass deconstruction potential in a foliage‐rich hot spring

Abstract: The ability of thermophilic microorganisms and their enzymes to decompose biomass have attracted attention due to their quick reaction time, thermostability, and decreased risk of contamination. Exploitation of efficient thermostable glycoside hydrolases (GHs) could accelerate the industrialization of biofuels and biochemicals. However, the full spectrum of thermophiles and their enzymes that are important for biomass degradation at high temperatures have not yet been thoroughly studied. We examined a Malaysia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…For example, some bacteria in module I are involved in plant litter degradation. Fungal genera Mortierella 67 and Acremonium 68 , as well as bacterial genera Roseiflexus 69 and Rubrobacter 70 that contain various lignocelluloses, xylanases, and glycoside hydrolases, may play important roles in cellulose, hemicellulose, or lignin breakdown. The main taxa in module II may be involved in biogeochemical C- and N-cycles.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some bacteria in module I are involved in plant litter degradation. Fungal genera Mortierella 67 and Acremonium 68 , as well as bacterial genera Roseiflexus 69 and Rubrobacter 70 that contain various lignocelluloses, xylanases, and glycoside hydrolases, may play important roles in cellulose, hemicellulose, or lignin breakdown. The main taxa in module II may be involved in biogeochemical C- and N-cycles.…”
Section: Discussionmentioning
confidence: 99%
“…UICC B-76 and Paenibacillus cisolokensis LC2-13A T , respectively. The plant litter degrading ability of the thermophilic bacteria from the phylum Firmicutes also reported by Lee et al (2018). They found that the dominant phyla in the microbiota of degraded foliage from the deeper part of hot spring were Firmicutes and Proteobacteria.…”
Section: Screening Of Xylan-degrading Abilitymentioning
confidence: 54%
“…Thus, bacteria that possess xylanase could use it as an organic nutrient. According to Lee et al (2018), Actinobacteria was one of the classes that contributed to almost 69% of the total population in the degraded foliage microbiota from foliage-rich hot spring in Sungai Klah, Malaysia, based on metagenomic analysis. Our previous studies, Mawarid et al (2016) and Yokota et al (2016), have reported the xylan-degrading ability of thermophilic bacteria from the phylum Firmicutes isolated from litter in Cisolok geyser, e.g.…”
Section: Screening Of Xylan-degrading Abilitymentioning
confidence: 99%
“…Their quick reaction time, thermostability, and decreased risk of contamination are an adeptness of thermophilic microorganisms and their enzymes. Thus, a good source for isolating efficient biomass degrading thermophiles and thermozymes was a hot spring (Lee et al, 2018).…”
Section: Relative Abundancementioning
confidence: 99%